2018
DOI: 10.1080/15265161.2018.1431322
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Consent: Building Trusting Relationships With Diverse Populations in Precision Medicine Research

Abstract: With the growth of precision medicine research on health data and biospecimens, research institutions will need to build and maintain long-term, trusting relationships with patient-participants. While trust is important for all research relationships, the longitudinal nature of precision medicine research raises particular challenges for facilitating trust when the specifics of future studies are unknown. Based on focus groups with racially and ethnically diverse patients, we describe several factors that infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
181
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(189 citation statements)
references
References 57 publications
(73 reference statements)
8
181
0
Order By: Relevance
“…The most prominent difference in perceived drivers of personal health was found in African American/Black participants' higher responses that discrimination and ethnicity/ race play an important role in their personal health. This is consistent with a large body of work highlighting the inequities and discrimination ethnic/racial minority groups often experience in the healthcare system (Dickman et al ; Institute of Medicine ; Williams et al ) and recent research demonstrating the specific role cultural experiences have on precision medicine perceptions (Kraft et al ). While Hispanic/Latino groups also experience health disparities and discrimination within the healthcare system (Dickman et al ; Institute of Medicine ; Williams et al ), in this study, no significant differences were found between Hispanic/Latino and White participants in their perceptions of the role that discrimination and ethnicity/race plays in their personal health.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The most prominent difference in perceived drivers of personal health was found in African American/Black participants' higher responses that discrimination and ethnicity/ race play an important role in their personal health. This is consistent with a large body of work highlighting the inequities and discrimination ethnic/racial minority groups often experience in the healthcare system (Dickman et al ; Institute of Medicine ; Williams et al ) and recent research demonstrating the specific role cultural experiences have on precision medicine perceptions (Kraft et al ). While Hispanic/Latino groups also experience health disparities and discrimination within the healthcare system (Dickman et al ; Institute of Medicine ; Williams et al ), in this study, no significant differences were found between Hispanic/Latino and White participants in their perceptions of the role that discrimination and ethnicity/race plays in their personal health.…”
Section: Discussionsupporting
confidence: 85%
“…African Americans/Blacks in our sample were almost twice as likely as Whites (30.2 vs. 16.1%) to report valuing payment for blood and tissue donations. Some of this difference may be related to historical discrimination African Americans/Blacks have experienced in prior research (e.g., United States Public Health Service Syphilis Study at Tuskegee and the Henrietta Lacks case), which has been shown to be related to distrust in precision medicine initiatives (Kraft et al ). Our analysis, however, found that African American/Blacks in our study population did not consider trust to be more important than Whites when deciding to get a genetic test.…”
Section: Discussionmentioning
confidence: 99%
“…Second, research on racial/ethnic minorities has identified a "spillover effect," whereby decisions to participate in PMR are inextricable from personal and group experiences of racism and discrimination in biomedical research and clinical care [51]. Participants' comments in our study may suggest that the spillover may encompass, on the one hand, negative experiences of ableism in research and medicine (e.g., inaccessibility, history of eugenics) and, on the other hand, decisions about return of genetic and other results from PMR.…”
Section: Future Directionsmentioning
confidence: 99%
“…Because NCI‐designated cancer centers deploy resources to community outreach and engagement efforts, community engagement becomes increasingly central to research efforts to decrease cancer incidence and mortality in defined catchment areas. Several strategies for creating impactful precision research agendas and building trustworthy relationships have been outlined by Dang et al and Kraft et al…”
mentioning
confidence: 99%
“…17 Because NCI-designated cancer centers deploy resources to community outreach and engagement efforts, community engagement becomes increasingly central to research efforts to decrease cancer incidence and mortality in defined catchment areas. Several strategies for creating impactful precision research agendas and building trustworthy relationships have been outlined by Dang et al and Kraft et al 11,18 Despite several important contributing demographic and health care factors raised by Barrett et al that impact participation in research or the donation of biospecimens, 9 other factors merit future consideration and investigation. For example, although awareness of the cultural diversity within ethnic subgroups may contribute to understanding research decisions among these subgroups, some ethnic groups with small national representation often are grouped together, or hidden.…”
mentioning
confidence: 99%